Peranan harapan, ketahanan dan faktor-faktor psikologi dalam menghadapi krisis kerjaya: meneroka implikasi pandemik Covid-19 ke atas perniagaan perunding motivasi - Muhammad Izzat Ebrahim,; Chong, Sheau Tsuey,; Muhammad Syaril Anwar Mustaza,; Juliana Rosmidah Jaafar, (Penerbit Universiti Kebangsaan Malaysia, 2023)
The global COVID-19 pandemic has caused unprecedented disruptions, resulting in widespread career crises and profound economic impacts. This study investigates the effects of the pandemic on the businesses of motivational consultants, with a specific focus on the interplay between hope, resilience, and various psychological factors. Through in-depth interviews with five participants from Selangor, we explore the challenges and experiences faced by motivational consultants during the pandemic. The study reveals significant consequences, including disruptions in daily business operations, financial challenges, and the enduring effects of containment measures. Additionally, we examine the role of hope, optimism, self-efficacy, and resilience in assisting motivational consultants in navigating the crisis and adapting their businesses. Findings deepen our understanding of how psychological factors influence career resilience in times of adversity. Moreover, the study highlights the crucial role of coping strategies and psychological capital in equipping individuals with the necessary resilience and resources. Future research should aim to include a larger sample size to enhance the generalizability of the findings. The implications of this research provide valuable insights for designing interventions and support systems that foster hope and resilience within the entrepreneurial community, enabling entrepreneurs to effectively face and overcome future crises.